Optimalisasi Usaha Agroindustri Tahu di Kota Pekanbaru - Sarifudin, Akhmad; Bakce, Djaimi; Maharani, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this study to analyze the right combination of products for tofu agroindustry businesses in order to achieve optimal conditions and analyze the allocation of resources owned by tofu agro-businesses to achieve optimal conditions. The data used in this study are primary and secondary data. This research method using a sensus method. The analytical method used are the optimization analysis and sensitivity analysis using the model of Linear Programming. These results indicate that in order to achieve optimal conditions, tofu agroindustry businesses in Pekanbaru City must produce the large tofu and the little tofu as much 339,242.1 units and 0 unit. From that total production is obtained profit per month of IDR 77,971,390. Resources that become active resource that is tofu acid resource, while other resources are passive or excess resources. Keywords: Tofu, Combination of Products, Resources